GARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA HOTEL MONA PLAZA PEKANBARU - Dian Aprilia; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by the importance of human resource management in the development and progress of the company. In a company, good human resource management is one way to increase employee productivity. To produce high work productivity, we need the best workforce to anticipate the opportunities and challenges of an increasingly competitive business environment. This research was conducted at Hotel Mona Plaza Pekanbaru, Jalan HR. Soebrantas, KM.18, Pekanbaru. The purpose of this study was to determine the level of work productivity of employees at Hotel Mona Plaza Pekanbaru. The sample of this study was taken as many as 31 respondents who are all employees of the Hotel Mona Plaza Pekanbaru, using the total sampling method. In this research, the method used is descriptive and quantitative. The data obtained from the results of interviews and the distribution of questionnaires/questionnaires were then statistically tested through the SPSS program. The analytical method used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that the work environment has a positive and significant effect on employee work productivity, work motivation has a positive and significant effect on employee productivity and the work environment and work motivation has a positive and significant effect on employee productivity at Mona Plaza Hotel Pekanbaru. Keywords: work environtment, work motivation, employee productivity